Soil Amendments with Organic Matter for The Control of Hollow Stalk (Pectobacterium carotovorum subsp. carotovorum) of Besuki Cigar Tobacco - Yulianti, Titiek; Hidayah, Nurul (AGRIVITA, Journal of Agricultural Science, 2011)
Amendments of soil with organic matter have been known to provide control of soilborne pathogens and to improve soil properties as well. Four sources organic matter, viz: rice straw, neem cake, chicken, and cow manure were amended one month prior to planting in soil naturally infested by Pectobacterium carotovorum subsp. carotovorum, the causal agent of hollow stalk of tobacco. Soil without added organic matter served as control and seedlings treated with streptomycin sulphate was used as a comparison. This treatment was combined with one of two sources of fertilizer N viz:, urea, and CaNO3. The field experiment was conducted in North Jember arranged in randomized blocked factorial with three replicates. The chicken manure amendment gave the best control of hollow stalk with lowest disease severity (12.03%) compared to other organic matter treatments or even control (31.31%). Chicken manure also improved plant height, yield, and the quality of flue cured tobacco. All organic matter treatments increased soil microbial populations of fungi, bacteria, and actinomycetes. This may be related to the suppression of the pathogen and the consequent reduction of disease severity. Treatment of soil with urea or CaNO3 showed no effect on disease severity or growth or quality of tobacco. Keywords : organic matter amendments, hollow stalk, Pectobacterium carotovorum subsp. carotovorum